The global drivers of wildfire - Haas, Olivia; Keeping, Theodore; Gomez-Dans, José; Prentice, I. Colin; Harrison, Sandy P. (Frontiers in Environmental Science, 2024)
Changes in wildfire regimes are of growing concern and raise issues about how well we can model risks in a changing climate. Process-based coupled fire-vegetation models, used to project future wildfire regimes, capture many aspects of wildfire regimes poorly. However, there is now a wealth of information from empirical studies on the climate, vegetation, topography and human activity controls on wildfire regimes. The measures used to quantify these controls vary among studies, but certain variables consistently emerge as the most important: gross primary production as a measure of fuel availability, vegetation cover as a measure of fuel continuity, and atmospheric humidity as a measure of fuel drying. Contrary to popular perception, ignitions are generally not a limiting factor for wildfires. In this review, we describe how empirical fire models implement wildfire processes, synthesise current understanding of the controls on wildfire extent and severity, and suggest ways in which fire modelling could be improved.• Empirical analyses of the controls on wildfires consistently identify vegetation properties associated with fuel availability and continuity and climate factors associated with fuel drying as the most important influences on wildfire extent and severity. • Ignitions, whether anthropogenic or natural, are generally not limiting.• Fire size, burnt area and fire intensity are influenced by different factors; current relationships between these aspects of wildfire could become decoupled in an altered climate. • Some hypotheses embedded in 'process-based' fire-vegetation models are inconsistent with empirical evidence, implying a need for a re-design.